Economic Optimality of Automatic Generation Control in a Multi-Source Power System Using an Optimization Problem Approach - Tambun, Laura Agnes; Fitri, Ismi Rosyiana (International Journal of Electrical, Computer, and Biomedical Engineering, 2025)
Due to the incorporation of a high penetration of renewable energy resources into power generation, recent power system control strategies have combined economic dispatch (ED) and automatic generation control (AGC) to achieve economic operation. To this end, AGC parameters and control laws have been designed to optimize operation through the use of optimization approaches. Although existing studies indicate that the proposed AGC optimal control strategy offers superior performance compared to traditional AGC, the models used in these theoretical frameworks are typically dominated by a single energy source, such as a steam-turbine generator. Additionally, the models in existing studies do not consider the ramp generation constraints present in practical implementations. In this paper, we propose an algorithm to obtain the optimal AGC parameters to consider a more realistic power system with diverse sources. Numerical simulations are used to demonstrate the effectiveness of the proposed method.